Effects of swirling combustion on soot characteristics in 2, 5-dimethylfuran/n-heptane diffusion flames. (5th July 2018) - Jia, Penghui; Ying, Yaoyao; Luo, Minye; Jiang, Bo; Liu, Dong
Highlights: Soot nanoscale properties in DMF/ n -heptane swirling and non-swirling flames are obtained. Soot reactivity in non-swirling flame is higher than that in swirling flame with 20% and 50% DMF additions. Effects of collection time on soot reactivity become obvious with increase of DMF additions. High correlations are found between soot nanostructure and reactivity. Abstract: Soot particles emitted from the combustion of engines and furnaces threaten human health gravely. The present work focuses on the nanostructure and oxidation reactivity of soot particles formed from 2, 5-dimethylfuran (DMF)/ n -heptane non-swirling and swirling flames. Effects of swirling and collection time on the nanostructure and oxidation reactivity of soot particles under the conditions of different 2, 5-dimethylfuran (DMF)/ n -heptane blending ratios were investigated in details using the high resolution transmission electron microscopy (HRTEM), X-ray diffraction (XRD), and thermogravimetric analysis (TGA). Results demonstrated that soot from 50% n -heptane/50% DMF flame presented a typical core–shell structure with larger planar lamellae, while partly graphitic and partly amorphous structures were found in soot from pure n -heptane and 80% n -heptane/20% DMF flames. Swirling combustion could strengthen the mixability of the oxidizer stream and fuel stream, decreasing the existence of reactive soot particles from the flames doped with 20% and 50% DMF. More reactive soot particles were collected by pure n -heptane swirling flame due to the reduction of residence time. The effect of collection time was non-significant on soot particles from pure n -heptane and 80% n -heptane/20% DMF flames. However, for soot particles from the 50% n -heptane/50% DMF flames, the graphitization degree was increased obviously with the increase of collection time due to the oxidizing atmosphere provided during the collecting process.